Evaluasi Implementasi Layanan Bimbingan dan Konseling di SMAN 1 Padang Panjang: Studi Survei Kuantitatif - Mardiah, Suci Amelia; Syukur, Yarmis; T, Taufik (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Guidance and Counseling (GCC) services play a crucial role in supporting the all-round development of students. This study aims to evaluate the effectiveness of the implementation of nursery services in Padang Long High School 1 based on national regulations and professional practices. The study used a quantitative approach with a survey method involving kindergarten teachers and students as respondents. Results showed that nursery services had been run to standards, yet there was still room for development, particularly in the utilization of technology and internal coordination systems. These findings provide important implications for the development of nursery services that are responsive to contemporary educational challenges.